Empiric Usage of "Anti-Pseudomonal" Agents for Hospital-Acquired Urinary Tract Infections - Ori Rahat; Murad Shihab; Elhai Etedgi; Debby Ben-David; Inna Estrin; Lili Goldshtein; Shani Zilberman-Itskovich; Dror Marchaim (MDPI AG, 2022)
Hospital-acquired urinary tract infection (HAUTI) is one of the most common hospital-acquired infections, and over 80% of HAUTI are catheter-associated (CAUTI). Pseudomonas aeruginosa, as well as other non-glucose fermenting Gram negative organisms (NGFGN, e.g., Acinetobacter baumannii), are frequently covered empirically with "anti-Pseudomonals" being administered for every HAUTI (and CAUTI). However, this common practice was never trialed in controlled settings in order to quantify its efficacy and its potential impacts on hospitalization outcomes. There were 413 patients with HAUTI that were included in this retrospective cohort study (2017-2018), 239 (57.9%) had CAUTI. There were 75 NGFGN infections (18.2% of HAUTI, 22.3% of CAUTI). P. aeruginosa was the most common NGFGN (82%). Despite multiple associations per univariable analysis, recent (3 months) exposure to antibiotics was the only independent predictor for NGFGN HAUTI (OR = 2.4, CI-95% = 1.2-4.8). Patients who received empiric anti-Pseudomonals suffered from worse outcomes, but in multivariable models (one for each outcome), none were independently associated with the empiric administration of anti-Pseudomonals. To conclude, approximately one of every five HAUTI (and CAUTI) are due to NGFGN, which justifies the practice of empiric anti-Pseudomonals for patients with HAUTI (and CAUTI), particularly patients who recently received antibiotics. The practice is not associated with independent deleterious impacts on outcomes.